Effects of insomnia and non-vasomotor menopausal symptoms on coronary heart disease risk: a mendelian randomization study. Issue 2 (February 2023) - Lian, Ie-Bin; Sie, Jia Jyun; Chang, Chia-Chu; Fann, Cathy S.J.; Huang, Ching-Hui
Abstract: Background: Previous studies suggested that vasomotor symptoms were associated with an increasing risk of coronary heart diseases (CHD) but not clear with menopausal symptoms other than vasomotor symptoms. Given the heterogeneity and interrelationship among menopausal symptoms, it is not easy to make causal inferences based on observational studies. We performed a Mendelian randomization (MR) to investigate the association of individual non-vasomotor menopausal symptoms and the risk of CHDs. Methods: A sample of 177, 497 British women aged ≥51 years old (average age at menopause) without related cardiovascular diseases from the UK biobank is selected as our study population. Non-vasomotor menopausal symptoms, including anxiety, nervous, insomnia, urinary tract infection, fatigue, and vertigo, were selected as exposures based on the modified Kupperman index. Outcome variable is CHD. Results: In total, 54, 47, 24, 33, 22, and 81 instrumental variables were selected for anxiety, insomnia, fatigue, vertigo, urinary tract infection and nervous respectively. We conducted MR analyses of menopausal symptoms and CHD. Only insomnia symptoms increased the lifetime risk of CHD with OR 1.394 (p = 0.0003). There were no significant causal relationships with CHD and other menopausal symptoms. Insomnia near menopause age (45–50 years) does not increase the risk of CHD. However, postmenopausal (over 51) insomnia increases the risk of CHD. Conclusion: MR analyses support that among non-vasomotor menopausal symptoms, only insomnia symptoms may increase the lifetime risk of CHD. Insomnia at different ages near menopause has differential impacts on CHD risk.